A 20-Gene Expression Diagnostic Signature of Bovine Respiratory Disease in Cattle (Journal of Scientific Research, 2022)
Bovine Respiratory Disease (BRD) is a prevalent disease in cattle rearing systems globally with significant health and economic costs. Current diagnostic methods of BRD rely on subjective visual signs and physical examination, which are suboptimal. This study, therefore, aims to find a blood-based gene expression signature for the diagnostic identification of BRD in cattle. The Gene Expression Omnibus dataset, GSE152959, was downloaded and used for analysis. The analyses performed included differential gene expression (DGE), clustering and machine learning prediction. Ninety genes were differentially expressed in BRD samples compared to controls. The GSE150706 dataset was used as the test dataset for machine learning prediction. The DEGs identified clustered the GSE150706 samples with good accuracy. For the machine learning prediction, 92 % of correctly predicted samples were obtained using twenty genes as features. Therefore, the identified 20-gene expression signature has BRD diagnostic utility in cattle. This signature could potentially be used to develop standardized and reliable diagnostic tests of Bovine Respiratory Disease in cattle. Improved diagnostics will lead to early detection and treatment, reducing the health and economic costs associated with the disease. Further validation in larger cattle cohorts is required.